The Role of Education in Promoting Social Justice: A Systematic Literature Review - Mila Karina (Penelitian dan Pengembangan Ilmu, 2024)
Education policy plays an important role in promoting social justice, especially for marginalized communities. However, there are still significant gaps in synthesizing how education reforms in different countries contribute to social justice. This systematic literature review aims to analyze and synthesize existing research on the impact of educational policies and reforms on social justice outcomes for marginalized populations. Using a comprehensive search strategy across major academic databases such as Scopus, Web of Science, and Google Scholar, this review identified key themes related to access and inclusion, teacher training and development, resource allocation, curriculum reform, and community engagement . The findings show that although many countries have succeeded in improving access to education for marginalized groups, challenges remain in ensuring educational quality and long-term equality. Additionally, contextual factors such as political will, distribution of resources, and community involvement play a significant role in determining the success of such policies. This review highlights the need for ongoing policy adjustments as well as further research into the long-term impacts of education reform. Policy implications are discussed, with recommendations for designing inclusive and context-responsive educational systems that promote greater social justice.